MODEL POPULASI PENDEKATAN PERTUMBUHAN DAN INDEKS KONDISI Harpiosquilla raphidea WAKTU TANGKAPAN PADA PAGI HARI DI PERAIRAN UTARA PULAU TARAKAN - Tomy Chandra; Gazali Salim; Dhimas wiharyanto (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2015)
The research method uses descriptive method. The main variables to be measured in this study are variable length relationship in total and the total weight, variable carapace length and weight of the meat, the correlation length variable weight, condition index variable. Secondary variables of physical and chemical parameters will be measured in this study were pH, DO, temperature, salinity and brightness. Data collection techniques using survey research design. The sampling technique shrimp H.raphidea use way of